تحليل كتاب تعليم اللغة العربية للصف العاشر من المدرسة الثانوية الدينية - Mohammad Rozy Zamroni; Muhammad Iqbal Haris; Luthfi Anisatin; Kiki Safitri (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2022)
The educational curriculum is closely related to the level of learning success. One way of implementing the curriculum is to group textbooks according to core competencies and learning objectives. This research uses library research methods or literature research, in which case the researcher collects data from different sources such as books, journals, documents, journals, etc. Research Results This article describes the results of analyzing the appropriateness of the textbook for teaching Arabic to the tenth students with basic competencies as follows: (1) Describe the development of educational materials, (2) Describe the vitality of the textbook from the tenth secondary school, (3) The feasibility of the language of the book